Floristic composition and vegetation structure in Rimbo Panti Natural Forest, West Sumatera - RAZALI YUSUF; PURWANINGSIH PURWANINGSIH; GUSMAN GUSMAN (Society for Indonesian Biodiversity, 2005)
Study on floristic composition and vegetation has been carried out in natural forest Rimbo Panti, it is one of the remnant natural forest area in West Sumatera. The study was used quadrad method. Three sample permanent plots of 100x100 m were arranged at some altitudes (300 m, 500 m, and 700 m). Enumeration was done to all trees with diameter at breast height down to 5 cm dbh.The result of tree sampling at the location from 1059 individu totally was recorded 199 species, belong to 113 genera and 48 families with total basal area 29.16 mÂ². Whereas the three plots were located at the same hill but if it was saw based on Jaccards index showed that the value relatively low, that is as 58.7%. From the three plots represented that at 300 m alt. which higher people pressure has been invation species of Arenga obtusifolia seriously. Some common species in the forest could be grouping of the big five, among them Paranephelium nitidum, Villebrunea rubescens, Aglaia odoratissima, Drypetes longifolia and Cyathocalyx sumatranus. The classification height of tree was showed that the plots in hilly ecosistem are a lot of trees in layer A (emergent tree) with height reached 50 m tall.Key words: composition, structure, vegetation, natural forest, Rimbo Panti.